PENGARUH PEMBERIAN SERBUK KERING JAHE MERAH TERHADAP PASIEN DIABETES MELITUS TIPE 2 - Eliza Arman; Deddy Almasdy; Rose Dinda Martini (LLDIKTI Wilayah X, 2016)
Red ginger (Zingiber officinale var rubrum ) is a rhizome plant that is very popular as a spice and traditional medicine in Indonesian society. Ginger as a traditional medicine could be expected to lower blood glucose of patients with diabetes mellitus type 2. Diabetes mellitus is a disease of high prevalence in the world, including Indonesia. This disease is a group of metabolic diseases with the characterization of hyperglycemia that occurs due to abnormal insulin secretion, insulin action or both disorders. This study is a clinical trial with 33 respondents. Inclusion criteria were patients with type 2 diabetes mellitus by sex men and women at the age of 35-60 years . Exclusion criteria were patients with impaired liver, kidney, heart, stomach as well as pregnant and lactating mothers. treatment group getting dried red ginger powder with a dose of 3 grams per day with a standard medicines while the control group get a standard drug without dried red ginger powder. Both groups examined the fasting blood glucose (FBG) and 2-hour postprandial blood glucose (2PPBG) before and after treatment. Changes in the levels of GDP and 2PPBG tested by analysis of covariance (ANCOVA) with a significance value of p< 0.05. The conclusion is a dried red ginger powder can lower fasting blood glucose with significant value (p= 0.031 ) While dried red ginger powde GD2PP no effect on the value of significance (p = 0.514 )..Ke word : Red ginger, diabetes mellitus type 2, traditional medicine